Approaches to clinical development of combination medicines in the Russian Federation and the Eurasian Economic Union in view of the requirements of the current legislation - A. V. Dobrovolskiy (Регуляторные исследования и экспертиза лекарственных средств)
In recent years, there has been an increasing interest in the development of combination medicines (fixed drug combinations) containing two or more active ingredients in a single dosage form. Therefore, there is an urgent need to develop an optimal programme of pre-authorisation clinical trials for combination medicines. The aim of the paper was to summarise modern science-based approaches to clinical development of combination medicines and identify possible ways of their practical implementation, taking into account the requirements of the current legislation. The author reviewed scientific publications devoted to creation of fixed drug combinations and analysed the regulatory documents defining regulatory requirements for pre-authorisation clinical studies of medicines in the Eurasian Economic Union, the Russian Federation, and other countries. Based on the results of the analysis the author described the general regulatory requirements for planning clinical studies of combination medicines for the purpose of their subsequent authorisation in the Russian Federation (via the national procedure) and the Eurasian Economic Union (via the centralized procedure). The pre-authorisation clinical development programme should be designed individually for each combination medicine. The selection of an optimal clinical trial strategy will make it possible to obtain sufficient information on the efficacy and safety of a combination medicine for its subsequent authorisation.